MEASUREMENT OF THE HEAVY METAL CONTENT OF ZINC (Zn) and COPPER (Cu) FROM THE GREEN SEAWEED Caulerpa taxifolia and Caulerpa racemosa - Bhernama, Bhayu Gita (Indonesian Journal of Environmental Sustainability, 2024)
Aceh has a great potential in coastal areas because Aceh has a large source of marine biota, especially seaweed. The coast that has great potential for seaweed growth is Ulee Lheue Beach. Ulee Lheue Beach is a tourist area and port, so it tends to be exposed to heavy metals. Seaweed can absorb heavy metals easily and is used as a bioindicator of environmental pollution. The aim of this research was to measure the heavy metal content of Cu and Zn from the green seaweeds Caulerpa taxifolia and Caulerpa racemosa. The research method was carried out using a hydrothermal analysis digestion process using a hydrothermal-microwave analysis tool for 30 minutes. Metal content was analyzed using an Atomic Absorption Spectrophotometer (SSA). The results showed that the levels of heavy metals of Zn and Cu in Caulerpa taxifolia seaweed were 11.05 and 3.65 ppm. Furthermore, the levels of heavy metals Zn and Cu in the seaweed Caulerpa racemosa were 18.46 and 12.26 ppm. It can be concluded that Caulerpa taxifolia and Caulerpa racemosa can absorb heavy metals.